Development of Animated Video Media for Meaningful Learning - Yusriyani Mulyawati; Enceng Yana (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Meaningful learning media has an important role in helping learners process educational messages or meaningful learning materials. Therefore, it is important to pay attention to the characteristics of learners and learning materials. Currently, there are still many media that do not pay attention to the characteristics of students, for example in the delivery of market material. The purpose of this study was to describe the feasibility and effectiveness of Canva-assisted animated video media in economics subjects. This type of research is Research and Development (R&D) research by applying Thiagarajan's 4D development model which includes defining, designing, developing and disseminating. Data collection instruments used 1) material, media and language review and validation sheets, 2) student response questionnaires. The results of the study found that: 1) the development of Canva-assisted animated video learning media was declared feasible with a material validation percentage of 90%, media validation of 86%, and language validation of 91% so that the media was declared feasible to use as learning media, 2) the results of the student response questionnaire obtained a percentage of 93.5% so that the media was declared practical to use as learning media. Thus, the Canva-assisted animation video developed is declared feasible and can be one of the alternative media that can be used in learning economics, especially market material. Methods, Findings, and Conclusions.